Flood sensitivity of the Bavarian Alpine Foreland since the late Middle Ages in the context of internal and external climate forcing factors - O. Böhm; J. Jacobeit; R. Glaser; K.-F. Wetzel (Hydrology and Earth System Sciences, 2015)
This paper describes the flood sensitivity of the Bavarian part of the Alpine Foreland of Germany and addresses different questions concerning climate variability and flood frequencies, from the 14th century until today. The focal point of the paper is the flood frequency of the superordinate spatial unit of the Bavarian Foreland. Based on written historical sources, the flood history of the Alpine Foreland of Germany can be reconstructed back to the 14th century. One major result is the occurrence of "flood-rich" and "flood-poor" episodes in almost cyclical sequences. Flood-rich periods, before the 16th century based on limited available data, were recorded in the periods 1300–1335, 1370–1450, 1470–1525, 1555–1590, 1615–1665, 1730–1780, 1820–1870, and 1910–1955 as well as in a ninth period beginning in 1980. The flood-rich periods are characterized by longer flood duration. Most of the flood-rich and flood-poor periods (in particular the beginning and the end of them) can be connected to changes in natural climate variability. These include changing sunspot numbers (as a measure of solar activity), so-called Little Ice Age type events (LIATEs) as well as changes in the North Atlantic Oscillation (NAO). Climate signals from external forcing factors, which could be used to explain the changing flood frequencies in the Bavarian Alpine Foreland, end in 1930. Relationships within the climate system such as the correlation of flood frequencies with the NAO have changed during the transition from the post Little Ice Age period to the Modern Climate Optimum around 1930. Natural climate variability might have been overlaid by anthropogenic climate change.